2017
DOI: 10.1038/s41598-017-18459-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ENSO’s response to unforced variability and anthropogenic forcing using CESM

Abstract: Understanding how the El Niño-Southern Oscillation (ENSO) may change with climate is a major challenge, given the internal variability of the system and relatively short observational record. Here we analyze the effect of coupled internal variability on changes in ENSO under anthropogenic global warming using the Community Earth System Model (CESM). We present results from a ~5000 year control run with constant pre-industrial conditions and a 50-member climate change ensemble experiment, consisting of historic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…While the sequence of internal variability differs from simulation to simulation, external forcing is consistent for each member of the ensemble: CMIP5 historical radiative forcings from 1920 to 2005 and RCP8.5 from 2006 to 2100. This fact can be exploited to assess the strength of the externally forced signal relative to the uncertainty associated with internal variability within CESM‐LE (i.e., Deser et al, 2012; Vega‐Westhoff & Sriver, 2017). Further elaboration of the ensemble is discussed in Kay et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…While the sequence of internal variability differs from simulation to simulation, external forcing is consistent for each member of the ensemble: CMIP5 historical radiative forcings from 1920 to 2005 and RCP8.5 from 2006 to 2100. This fact can be exploited to assess the strength of the externally forced signal relative to the uncertainty associated with internal variability within CESM‐LE (i.e., Deser et al, 2012; Vega‐Westhoff & Sriver, 2017). Further elaboration of the ensemble is discussed in Kay et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…We present results from two climate change ensemble experiments using the low‐resolution version of CESM (Shields et al, ), introduced by Sriver et al (), Hogan and Sriver (), and Vega‐Westhoff and Sriver (). Each ensemble uses the same preindustrial control simulation with constant preindustrial radiative forcing, which was spun up with a full‐coupled atmosphere–ocean component, until the deep ocean had reached approximate dynamic equilibrium (by year 4200).…”
Section: Methodsmentioning
confidence: 99%
“…Climate models are often evaluated to provide information on changes in the deep ocean, and studies have found that ocean heat uptake contributes considerably to climate model spread (Bóe et al, 2009). Here we focus on quantifying the time scales of adjustment in the ocean using fully coupled, comprehensive model ensemble runs simulated by the Community Earth System Model (CESM; Sriver et al, 2015;Hogan & Sriver, 2017;Vega-Westhoff & Sriver, 2017;Haugen et al, 2018; -https://journals.ametsoc.org/doi/abs/ 10.1175/JCLI-D-17-0782.1). We evaluate ocean internal variability in temperature as a proxy for ocean adjustment and assess this variability on both global-and basin-scale spatial regions, and throughout different ocean depths.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the El Niño-Southern Oscillation (ENSO) can influence the atmospheric flow with its warmer than normal sea surface temperatures (SST) in the eastern central Pacific during its El Niño phase, or cooler than normal SST during its La Niña phase. These impacts will likely persist into the future, thus analysis of ENSO variability in climate models is a major area of current research (Bellenger et al, 2014), including estimating ENSO changes under parametric model uncertainties (Sriver et al, 2014) and internal variability (Vega-Westhoff & Sriver, 2017). ENSO can also influence severe and hazardous weather activity, such as tropical cyclones and tornadoes (Allen et al, 2015;Pielke & Landsea, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…ENSO can also influence severe and hazardous weather activity, such as tropical cyclones and tornadoes (Allen et al, 2015;Pielke & Landsea, 1999). These impacts will likely persist into the future, thus analysis of ENSO variability in climate models is a major area of current research (Bellenger et al, 2014), including estimating ENSO changes under parametric model uncertainties (Sriver et al, 2014) and internal variability (Vega-Westhoff & Sriver, 2017). Overall, knowledge acquired from these types of studies can then be applied to improve the operational models that forecast ENSO phases from the next month to the next year, ultimately helping countries prepare for the impending impacts (Chapman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%